If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14a + 3 = 11 + -2a Reorder the terms: 3 + 14a = 11 + -2a Solving 3 + 14a = 11 + -2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2a' to each side of the equation. 3 + 14a + 2a = 11 + -2a + 2a Combine like terms: 14a + 2a = 16a 3 + 16a = 11 + -2a + 2a Combine like terms: -2a + 2a = 0 3 + 16a = 11 + 0 3 + 16a = 11 Add '-3' to each side of the equation. 3 + -3 + 16a = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 16a = 11 + -3 16a = 11 + -3 Combine like terms: 11 + -3 = 8 16a = 8 Divide each side by '16'. a = 0.5 Simplifying a = 0.5
| -x+6y=6 | | x=13-3y | | 217-6x=39x+22 | | 4x^5+2x^3+3x^4= | | z(2z-3)=14 | | 5x+9y=29 | | -5p-3(4-4p)=2(p-5)-47 | | (3x-1)(3x-1)=5(x-2)+(x+1)(5x+2) | | a^2-14a=-45 | | 2(3+5x)-2=64 | | .40n+.70(60-n)=31.2 | | 6(v+1)-2v=2(2v+1)-9 | | 4p+9q+5p-3q= | | 3y^2+8y-9=2y | | 4(2t-4)=32-4t | | 1-2x=3x+11 | | 6x+9=108-5x | | 8x^3(3x^2+2y)= | | 9-8x=109-36x | | 16x[3x-(6-9x)]=30x+[-(3x+2)-(x+3)] | | 8h+4(5g+2h)= | | 34-6x=3x+18 | | 13-7x=173-35x | | 9n-6=39 | | 3x+[-5x-(-x+3)]=8x+(-5x-9) | | .40x+.25(81-x)=26.7 | | 5x+6=4x | | 2(4g+3)=4(3g-5) | | 41-6x=3x+22 | | x+9=18-2x*x | | 52-3x=6x+23 | | .25x+.40(81-x)=26.7 |